Hubungan Rasio Panjang Jari Telunjuk dan Jari Manis (2D:4D) dengan Tinggi Badan Mahasiswa Universitas Jambi - Adinda Kinantia Gayatri; Amanda Rya Agustyn; Dea Abyanti Putri; Priska Enjelina Napitu; Jodion Siburian; Evita Anggereini; Saparuddin Saparuddin; Ine Tentia (Biocaster : Jurnal Kajian Biologi, 2026)
The finger length ratio (2D:4D) is often used as an indirect indicator to estimate the influence of hormones, especially prenatal sex hormones, which are thought to be related to physical variations such as height. This study aims to analyze the relationship between the index finger and ring finger length ratio (2D:4D) and the height of students at the University of Jambi. This study used a quantitative approach with a correlational design. The sample consisted of 37 students at the University of Jambi who were selected using purposive sampling. The inclusion criteria included students who were willing to participate, were in good physical health, and had no growth disorders or abnormalities of the fingers. Measurements were taken directly of the length of the index finger (2D) and ring finger (4D) on the right and left hands using calipers with an accuracy of 0.05 mm, while height was measured using a tape measure. Pearson's correlation analysis was used to determine the relationship between the 2D:4D ratio and height. The results showed that the relationship between height and the 2D:4D ratio on the right hand (r = 0.184; p = 0.276) and left hand (r = 0.233; p = 0.166) was positive but very weak and not statistically significant. These findings indicate that the 2D:4D ratio is not significantly related to the height of students at the University of Jambi.